Dietary supplementation with farnesol confers a protective effect on the intestine of broiler chickens challenged with lipopolysaccharide by reshaping intestinal flora structure and regulating TLR4/NF-κB signaling pathway - Peng Li; Chenyu Guo; Wenfei Tong; Shaochen Han; Xiangxue Sun; Lei Xiao; Qunbing Hu; Yongqing Hou; Binying Ding; Dan Yi (Poultry Science)
Farnesol (FAN), one of plant essential oils, is widely found in a variety of natural plants. Studies demonstrated that FAN contributed to the antioxidant and immune function as well as improving the intestinal flora, however effects of it on the broiler chickens has not been fully characterized. In the present study, we present an undated report of its effects on growth performance, antioxidant and immune functions of broiler chickens challenged with lipopolysaccharide (LPS). One hundred healthy male AA+ broiler chickens with uniform body weight were divided into control and FAN groups, there were five replicates and 10 birds in each one. The trial lasted for 28 days, and two birds with uniform body weight were selected from each replicate to be treated with intraperitoneal injection of LPS at the end of the trial, and then samples were harvested after 3 h. Results showed that dietary supplementary with FAN tended to improve the feed conversion ratio (FCR) (P = 0.058). The levels of serum lactate dehydrogenase and IL-1β were elevated in the birds challenged with LPS, as well as the content of malondialdehyde in the ileal and liver (P < 0.05). Additionally, LPS treatment descended the levels of catalase and superoxide dismutase, and the ratio of villi height to crypt depth in the ileum (P < 0.05). Dietary supplementation with FAN was able to alleviate the abnormal changes of the above indexes caused by LPS. In addition, dietary supplementation with FAN also contributed to alleviating the up-regulation of Toll-like receptor 4 (TLR-4), nuclear transcription factor κB (NF-κB), myeloid differentiation primary response gene 88 (MYD88), tumor necrosis factor (TNF-α) and IL-1β transcription levels in the ileum and liver of birds challenged with LPS (P < 0.05). Results of intestinal flora demonstrated that the relative abundance of Candidatus Arthromitus was up-regulated in the ileal chyme of birds challenged with LPS, and dietary supplementation with FAN could reshape it. Intriguingly, the relative abundance of Candidatus Arthromitus was positively correlated with the mRNA levels of TLR-4, NF-κB, MYD88, TNF-α and IL-1β in the ileum (P < 0.05). In conclusion, dietary supplementation with FAN might confer a protective effect on the intestine of broiler chickens challenged with lipopolysaccharide by reshaping intestinal flora, especially Candidatus Arthromitus, and regulating TLR4/NF-κB signaling pathway.